Spectrophotometric Determination of Raloxifene Hydrochloride in Pharmaceutical Formulations - M. Mathrusri Annapurna; M. E. Bhanoji Rao; B. V. V. Ravi Kumar (E-Journal of Chemistry)
Three new simple, sensitive, rapid and economical spectrophotometric Methods (A, B and C) have been developed for the determination of Raloxifene Hydrochloride in pharmaceutical bulk and tablet dosage form. Method A is based on the formation of yellow colored chromogen with 0.1N Sodium hydroxide exhibiting maximum absorbance against the corresponding reagent blank. The method B is based on the reaction of Raloxifene with Ferric chloride and 1, 10-phenanthroline to form blood red colored chromogen. The method C is based on the formation of blood red colored chromogen with Ferric chloride and 2, 2' bipyridyl. The absorbencies of the chromogens were measured at their respective wavelength of maximum absorbance against the corresponding reagent blank. The proposed methods have been successfully applied to the analysis of the bulk drug and its tablet dosage form. The methods have been statistically evaluated and were found to be precise and accurate.